HOW FRANKL'S MAN'S SEARCH FOR MEANING SHAPES OUR UNDERSTANDING OF LOGOTHERAPY - Botilca, Cristina Mihaela (Sanata Dharma University, Yogyakarta, 2024)
Viktor Frankl's Man's Search for Meaning is a major book in existential psychology, which offers a deep understanding of the human search for meaning during suffering. In this article, I will delve into how and where contemporary psychological practices are greatly impacted by Frankl's logotherapy. The paper commences with an analysis of Frankl’s life and his work within the historical context showing how the experiences he went through in Nazi concentration camps influenced his theoretical perceptions. Furthermore, it looks at some principles of logotherapy such as personal voids and desire for meaning in order to discuss their role in treating trauma and building up people’s resistance power. Lastly, it underscores logotherapy’s amalgamation with other therapeutic modalities, its influence on positive psychology as well as its wider applications within healthcare systems and schools among others. This paper provides a detailed examination of Frankl’s principles that remain very useful in promoting mental healthiness and self-improvement thus affirming how meaningfulness can be used to respond to human pain.